PENGARUH PENGGUNAAN LKPD BERBANTUAN MEDIA PHET SIMULATION TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI RANGKAIAN LISTRIK KELAS IX DI MTs NEGERI 8 KAMPAR - Velya Aristi; Fakhruddin. Z Fakhruddin. Z; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the effect of using the PHET-assisted LKPD on students' understanding of the concept of electrical circuit material for class IX at MTs Negeri 8 Kampar. This study involved 15 students of class IX.1 MTsN 8 Kampar. The instrument used is LKPD in the form of a description. Data were collected through 3 learning stages using LKPD, namely, pre LKPD, during LKPD, and discussion. Each scattered item has 3 indicators, namely electric current, open circuit, and closed circuit. Then the research results were analyzed descriptively. The results showed that learning using LKPD assisted by PhET media was able to improve students' understanding of concepts in electrical circuit material. This can be seen from the increase in the percentage of students' correct answers at the average percentage in each stage of learning.Keywords: LKPD, Phet simulation, understanding the concept